2007
DOI: 10.1073/pnas.0606557104
|View full text |Cite
|
Sign up to set email alerts
|

Determining the stoichiometry of protein heterocomplexes in living cells with fluorescence fluctuation spectroscopy

Abstract: FFS is an attractive candidate for studying protein interactions in cells and is based on fluctuations in the fluorescence intensity observed in a small observation volume (Ͻ1 fl) that are due to individual proteins entering or leaving the volume (1). Fluorescence correlation spectroscopy (FCS) uses correlation functions to determine the concentration and temporal properties of proteins, and dual-color FCS has been used to detect protein interactions in cells (2, 3). However, a quantitative characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…1C). This result agrees with an earlier study where it was shown that the NID fragment of steroid receptor coactivator-1, which contains the three NR boxes, is able to bind three RXRLBD (9). Whereas the earlier study was limited to a coactivator fragment, the present data show the same surprising result for the full-length coactivator.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1C). This result agrees with an earlier study where it was shown that the NID fragment of steroid receptor coactivator-1, which contains the three NR boxes, is able to bind three RXRLBD (9). Whereas the earlier study was limited to a coactivator fragment, the present data show the same surprising result for the full-length coactivator.…”
Section: Resultssupporting
confidence: 93%
“…Our experiments identify a nontrivial 3∶1 stoichiometry between RXRLBD and TIF-2 in the presence of agonist (Fig. 1C), which agrees with a previous study limited to the NID fragment of a related coactivator (9). If both proteins are full-length, a change in the stoichiometry occurs with two RXR bound to the coactivator TIF-2 (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations